Kajian Terhadap Bentuk Pertanggungjawaban dan Sanksi Pidana Korporasi Dalam Tindak Pidana Penyelundupan - Salma Salsabila; salsabila, salma; Bambang Herlambang Irawan Nurraid; Kartika Justia Dwiningrum; Savira Putri Rhaudah (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2022)
This study aims to provide an understanding of the forms of liability and corporate criminal sanctions in the crime of smuggling and how the rules regarding smuggling can be seen from the general criminal aspect as well as economic offenses. This study uses a normative juridical research method. The results of this study are first, economic offenses or economic crimes are a form of special criminal law listed in the Criminal Code. Second, the smuggling offense is an act that violates the regulations in the RechtenOrdonnatie Stb. 1882 No. 240 which has been amended or added to the act, where the rules in casu can be threatened with a criminal.